2003
DOI: 10.1172/jci200316584
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of type 1 diabetes mellitus in proinsulin 2–deficient NOD mice

Abstract: Accumulating evidence favors a role for proinsulin as a key autoantigen in diabetes. In the mouse, two proinsulin isoforms coexist. Most studies point to proinsulin 2 as the major isoform recognized by T cells in the NOD mouse. We studied mice in which a null proinsulin 2 mutation was transferred from proinsulin 2-deficient 129 mice onto the NOD background along with 16 genetic markers (including I-A g7 MHC molecule) associated with diabetes. Intercross mice from the fourth backcross generation showed that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 34 publications
2
54
0
1
Order By: Relevance
“…Most autoreactive T cell targets are beta cell specific, including glucose-6-phosphatase catalytic subunit 2 (G6PC2, also known as IGRP) and solute carrier family 30 member 8 (SLC30A8 also known as ZNT8); others are not entirely restricted to beta cells, including chromogranin A and PTPRN. Studies in NOD mice have shed some light on the relative roles of individual autoantigens: deletion of either proinsulin gene alters diabetes progression in NOD mice (Moriyama et al 2003, Thébault-Baumont et al 2003, Nakayama et al 2007, whereas deletion of GAD or PTPRN does not alter disease progression (Yamamoto et al 2004, Kubosaki et al 2005.…”
Section: Iapp As An Autoantigen In Type 1 Diabetesmentioning
confidence: 99%
“…Most autoreactive T cell targets are beta cell specific, including glucose-6-phosphatase catalytic subunit 2 (G6PC2, also known as IGRP) and solute carrier family 30 member 8 (SLC30A8 also known as ZNT8); others are not entirely restricted to beta cells, including chromogranin A and PTPRN. Studies in NOD mice have shed some light on the relative roles of individual autoantigens: deletion of either proinsulin gene alters diabetes progression in NOD mice (Moriyama et al 2003, Thébault-Baumont et al 2003, Nakayama et al 2007, whereas deletion of GAD or PTPRN does not alter disease progression (Yamamoto et al 2004, Kubosaki et al 2005.…”
Section: Iapp As An Autoantigen In Type 1 Diabetesmentioning
confidence: 99%
“…In mice, two isoforms of pro-insulin exist, and pro-insulin-2 represents the principle isoform targeted during autoimmune reactions. Thébault-Baumont et al [27] demonstrated that NOD mice, which are deficient for pro-insulin-2, develop accelerated insulitis and diabetes. This may be correlated with a lack in the peripheral T cell repertoire, due to the absence of pro-insulin-2 within the thymus.…”
Section: Negative Selection and Autoimmunity: Promiscuous Gene Expresmentioning
confidence: 99%
“…This may be correlated with a lack in the peripheral T cell repertoire, due to the absence of pro-insulin-2 within the thymus. Furthermore, allelic variations of pro-insulin correlate with the risk of T1D in humans, while insulin expression within the thymus promotes T cell tolerance to insulin in mice [27]. …”
Section: Negative Selection and Autoimmunity: Promiscuous Gene Expresmentioning
confidence: 99%
“…Mice that were engineered to have a graded thymic insulin deficiency, while pancreatic insulin remained unaltered, exhibited a detectable peripheral T-cell response to proinsulin even against a nondiabetogenic background [36, 37]. Bred against the NOD background, these mice show marked acceleration of insulitis and diabetes [38]. Importantly, enhanced reactivity in these mice was confined to insulin and did not affect autoimmunity against other autoantigens.…”
Section: Ins-vntr (Iddm2)mentioning
confidence: 99%